Interpretative potential of dental metrics for biodistance analysis in hunter-gatherers from central Argentina. A theoretical-methodological approach - Luna, Leandro Hernan (2015)
The use of dental metrics as a reliable tool for the assessment of biological distances has diversified dramatically in the last decades. In this paper some of the basic assumptions on this issue and the potential of cervical measurements in biodistance protocols are discussed. A sample of 1173 permanent teeth from 57 male and female individuals, recovered in Chenque I site (western Pampas, central Argentina), a Late Holocene hunter-gatherer cemetery, is examined in order to test the impact of exogenous factors that may have influenced the phenotypic manifestation and affected dental crown sizes. The statistical association between dental metric data, obtained by measuring the mesiodistal and buccolingual diameters of the crown and cervix, and the quantification of hypoplastic defects as a measure to evaluate the influence of the environment in the dental phenotypic expression is evaluated. The results show that socioenvironmental stress did not affect dental metrics and that only the more stable teeth (first incisors, canines, first premolars and first molars) and three variables (buccolingual diameter of the crown and both mesiodistal and buccolingual measurements of the cervix) should be included in multivariate analyses. These suggestions must be strengthened with additional studies of other regional samples to identify factors of variation among populations, so as to develop general guidelines for dental survey and biodistance analysis, but they are a first step for discussing assumptions usually used and maximizing the available information for low-density hunter-gatherer societies.